Is Prolonged Copper Restriction Needed in Pediatric Wilson’s Disease? - Hizarcıoğlu-Gülşen, Hayriye; Şimşek Onat, Pınar; Yıldırım, Damla; Demirtaş, Duygu; Boyraz, Meryem S.; Göktaş, Mehmet A.; Demir, Hülya; Özen, Hasan; Saltık-Temizel, İnci Nur (Turkish Journal of Gastroenterology, 2022)
Background: Dietary copper restriction in Wilson’s disease is recommended mostly for 1 year or until showing normal liver enzymes. Little is known about the effect of long-term copper restriction on copper and nutritional status in the body. The relationship between daily copper consumption and serum and urine copper parameters, liver enzymes, and dietary contents was investigated. Methods: In this study, 32 pediatric Wilson’s disease patients who had been on treatment at least for 12 months were included. Clinical features, liver enzymes, serum total copper concentrations, non-ceruloplasmin bound copper concentrations, adjusted copper concentrations, 24-hour urine copper excretions, and macro- and micronutrient consumptions were analyzed. Results: In total, 27 patients reported following copper-restricted diets, while daily copper consumption was low only in 7 patients (21.9%). Total copper concentrations and non-ceruloplasmin-bound copper concentrations were low at 78.1% and 53.1%, respectively. All but one adjusted copper concentration were within normal limits. Total copper concentrations, adjusted copper concentration, and non-ceruloplasmin-bound copper concentrations correlated with each other but none correlated with urine copper excretions. Daily copper consumption was inversely correlated with total copper concentrations (P = .041, r = –0.363) but not correlated with non-cerulo plasmin-bound copper concentrations and adjusted copper concentrations. There was no relationship between liver enzymes and daily copper consumption and serum and urine copper parameters. High fat consumption with low fiber and vitamin B6 was more common in low daily copper consumption group (P = .033, P = .029, P = .007, respectively). Conclusions: Daily copper consumption may be the least effective or non-effective factor on liver enzymes in Wilson’s disease. Prolonged copper restriction may result in unintentional dietary imbalance. Avoidance of undernutrition and high-fat meals, as well as enrichment of the meals with vitamin B6 and fiber, should be encouraged during copper-restricted diets. Cite this article as: Hizarcıoğlu-Gülşen H, Şimşek Onat P, Yıldırım D, et al. Is prolonged copper restriction needed in pediatric Wilson’s disease? Turk J Gastroenterol. 2023; 34(1): 80-86.